Pain Acceptance Moderates the Relation Between Pain and Negative Affect in Osteoarthritis and Fibromyalgia Patients - Kratz, Anna L. (2007)
BACKGROUND: Chronic pain is often intractable despite advanced medical and psychotherapeutic treatments. Pain acceptance is emerging as a promising complement to control-based pain management strategies and a likely approach to maintaining quality of life for chronic pain patients. PURPOSE: This theoretically-based analysis of an existing database examined the extent to which pain acceptance predicted weekly reports of positive affect (PA) and negative affect (NA), and the relations of pain severity to both PA and NA. METHODS: Participants were women, 35 with osteoarthritis and 75 with fibromylagia, who completed an initial assessment for demographics, pain catastrophizing, and pain acceptance, and 8−12 weekly assessments of pain severity, PA, and NA. RESULTS: Multilevel modeling analyses indicated that pain acceptance was related to higher levels of PA but was unrelated to NA. Furthermore, pain acceptance moderated the relation of NA and pain severity, such that expected increases in NA during pain exacerbations were buffered by higher levels of pain acceptance. CONCLUSIONS: These findings suggest that pain patients with greater capacity to accept pain may be emotionally resilient in managing their condition.